Radiologic protection in the face of real danger of nuclear war - Andryskowski, Grzegorz (Contemporary Oncology/Współczesna Onkologia, 2003)
The present political situation in the world makes us aware of the real danger of the use of nuclear weapons. For over 50 years research has been conducted on the role of active oxygen in ionizing radiation-induced damage and on the estimation of antioxidants’ ability to decrease its harmful effect. For 30 years Walter Reed Army Institute of Research financed the program of development of radioprotective drugs. More than 4000 substances were synthetized and investigated. The aim of this study is to discuss compounds with radioprotective properties. Numerous compounds including a thiol group in their structure have antimutagenic and anticarcinogenic properties and protect against radiation-induced lethality. Developing WR-2721 (S-2- -(3-aminopropylamino)ethylphosphorothioic acid) was the most significant achievement. Protective action of compounds found in natural raw materials has been proved in numerous studies. They protect only against lower doses of radiation or against radiation of lower frequency. The advantage of natural antioxidants may be low toxicity and increased benefits resulting from the possibility of their longer application. Their antimutagenic effect is emphasized. Natural antioxidants frequently demonstrate a certain degree of protection when applied a few hours prior to or after exposure to radiation. Many drugs such as caffeine, nimodipine, propranolol, besides their basic pharmacologic action have additional antioxidative properties. All these compounds can be applied as radioprotective agents.